The Economic Theory as a Basis for Economic History Research (UNWE Yearbook, 2016)
The theoretical and methodological basis of the economic history research is characterized by a careful balance between the peculiar methods of economics and the specificities of the historical methodology. Since economic history is primarily economic, the economic way of thinking and the economic theory should have a leading position. They should serve as a theoretical basis or as an unavoidable context of each economic history research. This is so because in general, the theory is necessary for the history, and as such it precedes historical research. In this study the author has developed a system of indicators that allows an adequate choice of theoretical concepts for economic history research.